Academic Senate Minutes 2004-02-05 - Academic Senate:::::::::
Agenda approved. Minutes of 12/18/04 approved. Consent item: Change Biology M.A. to M.S approved. Information Items: End-of-Year report for Graduate Studies subcommittee '02-'03; Appointment of Marty Ruddell, Education to University Documents Committee of URTP. Report from Provost Ochoa. Permission to hold Senate election without requisite number of nominees approved. Long Range Academic Plan approved. Proposed FACULTY GOVERNANCE ASSIGNED TIME '04-'05 approved. Resolution regarding Lecturers Compensation for Service on Academic Senate approved. Resolution supporting Proposition 55 approved.